Hinduism in the Socio-Political Life of India - T. L. Shaumyan (Международная аналитика, 2021)
The article analyzes the importance of the religious factor in determining the ways of socio-political development of India. India remains a country with a multi-confessional population with a clear predominance of adherents of Hinduism. In addition to the infl uence of Hinduism on the life of orthodox society, where castes still play a special role, which determine the norms of behavior and rules of communication, the author analyzes the role of religion in the political agenda of the country. Under the conditions of colonialism, Hinduism was established as a national religion and the basis of a national tradition. The active involvement of Hinduism in political life began at the end of the nineteenth century, when such political parties as the Muslim League and Hindu Mahasabha appeared. The task of the latter was to create a Hindu state in India. The author also pays special attention to the analysis of the formation of the Bharatiya Janata Party, which is characterized as the political wing of a group of Hindu nationalist organizations. The growing popularity of this party, which won the elections in 2014 and 2019, indicates the strengthening of the positions of communalist organizations. These trends show that the active inclusion of religion in the political agenda aff ects the nature of the country’s democratic institutions, gradually transforming the popular thesis that India is a country representing “unity in diversity”.